British politics today: moral grounds as reflected in conceptual metaphor - Arcimavičienė, Liudmila (Kalbotyra, 2007)
The present study aims at examining the moral grounds of today’s British political life as reflected in conceptual metaphors of political discourse. The method applied to analyze the moral grounds is that of hypothetical deduction combined with the theoretical framework of cognitive linguistics (qualitative analysis). The research findings reveal that the underlying conceptual metaphor of British critical political discourse is that of POLITICS AS JOURNEY. The use of this metaphor shows the moral unacceptability of today’s British political life due to the failed moral obligations of British politicians.